2015
DOI: 10.1007/s40620-015-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal toxicity of anticancer agents targeting HER2 and EGFR

Abstract: EGFR and HER2 are found overexpressed and/or activated in many different human malignancies (e.g. breast and colon cancer), and a number of drugs specifically targeting these two tyrosine kinases have been developed over the years as anticancer agents. In the present review, the renal safety profile of presently available agents targeting either HER2 or EGFR will be discussed, together with the peculiarities related to their clinical use in patients with impaired renal function, or even in dialysis. Indeed, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…[123] The “nutraceutical” curcumin, the principal active polyphenolic pigment in the curry spice turmeric, obtained from the rhizome of Curcuma longa shows promise for a variety of conditions. [456]…”
mentioning
confidence: 99%
“…[123] The “nutraceutical” curcumin, the principal active polyphenolic pigment in the curry spice turmeric, obtained from the rhizome of Curcuma longa shows promise for a variety of conditions. [456]…”
mentioning
confidence: 99%
“…In humans, EGFR is upregulated and/or activated in various malignancies and suppression of EGFR activation is considered a valid strategy for tumor treatment (34,35). Akt and Erk are downstream signaling molecules of EGFR, and the aberrant activation of either triggers a cascade of proliferative responses (36). Akt and Erk phosphorylation are increased when EGFR is activated in RCC (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the renal toxicity of EGFR‐targeting agents is relatively uncommon and reversible. A review on the renal toxicity of anticancer agents targeting EGFRs suggested that kidney impairment and dialysis should not be regarded per se as reasons not to administer or stop active anti‐HER2 and anti‐EGFR anticancer treatment, especially given the possibility of significantly improving the life expectancy of many cancer patients because of these agents . However, with the increasing number of patients being treated by different EGFR‐targeting anticancer treatments, the features of each agent should be compared and reviewed for individualized patients with other underlying diseases.…”
Section: Case Descriptionmentioning
confidence: 99%